"Survive and Sustain": Adaptive and Innovative Library Instruction in the Time of COVID-19. Issue 2 (3rd April 2023) - Norton, Christina; Armstrong, Anne; Phares, Dee Anna; Allen, Kristin; Hall, Amy; Hayes, Tish
Abstract: This study surveys members of an Illinois state-wide consortium to chart changes to the instructional practices of academic librarians in response to the conditions brought on by the COVID-19 pandemic. The survey findings and analysis provide insights into changes made to multiple aspects of participants' teaching, such as modality, technology use, instructional design, and adjustments to students' socioemotional needs at a time of rapid change, disruption, and stress. In addition to exploring instructional adaptations of librarians, the study identifies gaps in institutional support that might be addressed at the consortial level. While librarians initially altered their teaching and instructional services in "emergency mode, " their reflections reveal that many changes could be beneficial and long-lasting, given adequate and sustained support.